1995
DOI: 10.1172/jci117816
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of G-protein alpha i2 subunit expression by oxidized low-density lipoprotein.

Abstract: Oxidized low-density lipoprotein (LDL) inhibits signalling pathways mediated by pertussis toxin-sensitive guanine nucleotide-binding proteins (GI proteins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 40 publications
6
26
0
1
Order By: Relevance
“…23 The higher intracellular levels of oxy-LDL in turn inactivate G i proteins and their ability to enhance the release of NO. 45,46 This interpretation implies that the augmented presence of A-FABP precedes the increase in oxidative stress causing the selective dysfunction in regenerated endothelial cells. The observations that BMS309403 potentiates, while apocynin only protects the response to the monoamine in preparations with regenerated endothelium favors the primary importance of A-FABP in causing the selective dysfunction of the G i proteins.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…23 The higher intracellular levels of oxy-LDL in turn inactivate G i proteins and their ability to enhance the release of NO. 45,46 This interpretation implies that the augmented presence of A-FABP precedes the increase in oxidative stress causing the selective dysfunction in regenerated endothelial cells. The observations that BMS309403 potentiates, while apocynin only protects the response to the monoamine in preparations with regenerated endothelium favors the primary importance of A-FABP in causing the selective dysfunction of the G i proteins.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this study, NO detection was performed in the presence of an excess of superoxide dismutase, thereby excluding the oxidative stress as a potential cause of the impairment in NO production by HC serum-treated cells in our experimental conditions. Aside from the inactivation of NO by reactive oxygen species, several studies examined the relationship between dyslipidemia and endothelial dysfunction through a direct modulation of eNOS expression and/or activation; they identified defects in the coupling of the receptor-G protein interaction leading to eNOS stimulation (6,36) and effects of oxidized LDL (oxLDL) on the steady-state mRNA levels of the enzyme (13,14). In the present study, these mechanisms are unlikely to account for the impairment in eNOS activity observed in endothelial cells exposed to HC serum or to high concentrations of isolated LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclei from EC (4 x 107 cells) exposed to the indicated 02 concentration from 12 h were isolated as described previously (18). In vitro transcription was carried out in a shaking water bath at 30°C for 30 min in a buffer containing 10 to NOS, pGEM, and ,3-tubulin were vacuum-transferred onto nylon membranes using a slot blot apparatus (Schleicher and Schuell).…”
Section: Methodsmentioning
confidence: 99%